The 7D BIM Modeling for Building Asset Data Management Using Revit, COBIe Extension, and QR code - Hatmoko, Jati Utomo Dwi; Taqy, Muhammad Ravy Arkan; Utama, Rahmana Pria; Hermawan, Ferry (Jurnal Sistem Informasi Bisnis, 2025)
The management of building asset data has experienced many problems related to accessibility and storage issues. This causes difficulties for asset managers in managing and developing buildings after the construction phase. This research aims to develop a 7D Building Information Modeling (BIM) model of buildings to facilitate access to asset data in operational and maintenance activities. Autodesk Revit was used to perform BIM modeling and was integrated with COBIe and the cloud via QR code. The Faculty of Engineering Building Diponegoro University was used as a case study. Data was collected through observation, project documents, as-built drawings, technical specifications, etc. This 7D BIM model with COBIe plug-in is expected to address gaps in asset management, improve operational efficiency, reduce the risk of damage, improve the ability to classify assets in a systematic and integrated manner, and improve collaboration between stakeholders to increase the effectiveness of asset management significantly.